Planʺ Petrozavodskoĭ guby Onezhskago ozera po opisi 1875 i 76 g.g. / Kopirovali khimicheskoi︠u︡ tushʹi︠u︡ K. Breĭtshprekherʺ - Russia. Gidrograficheskīĭ departament; (Sankt-Peterburg : Morskoe ministerstvo, Gidrograficheskīĭ departament; [Санкт-Петербург] : Морское министерство, Гидрографическій департамент, 1883)
Plan of Petrozavodsk Bay of Lake Onega.; Pulkovo meridian.; Relief shown by hachures and spot heights. Depths shown by soundings and isolines.; "Onezhskoe ozera." [Lake Onega] -- across top margin.; "Masshtabʺ 300 sazh. vʺ di︠u︡ĭmi︠e︡." [Scale 300 sazhens in 1 inch].; "No. 179" -- handwritten bottom right margin Grayscale; 1:25,200